2008
DOI: 10.1002/ajmg.b.30846
|View full text |Cite
|
Sign up to set email alerts
|

Variability of AChE, BChE, and ChAT genes in the late‐onset form of Alzheimer's disease and relationships with response to treatment with Donepezil and Rivastigmine

Abstract: Several factors are believed to give rise to the late onset sporadic form of Alzheimer's disease (LOAD). We have studied the variation at the genes of three enzymes of the cholinergic system: acetylcholinesterase, butyrylcholinesterase, and choline acetyltransferase. The single nucleotide polymorphisms (SNPs) examined were: AChE rs2571598, BChE rs1355534, BChE rs1803274, and ChAT rs2177369. The sample for the case-control study was 471 LOAD patients aged 60 years or older, and 254 subjects with no neurodegener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 18 publications
3
54
3
Order By: Relevance
“…One other report found that BCHE genotype did not influence response to ChEI treatment. 50 However, only change in MMSE was reported and not disease severity, making comparison with previous reports and this study difficult. A recent study has suggested an explanation for these seemingly incongruous findings.…”
Section: Apoe Bche and Chei Treatment Response In Adcontrasting
confidence: 58%
See 1 more Smart Citation
“…One other report found that BCHE genotype did not influence response to ChEI treatment. 50 However, only change in MMSE was reported and not disease severity, making comparison with previous reports and this study difficult. A recent study has suggested an explanation for these seemingly incongruous findings.…”
Section: Apoe Bche and Chei Treatment Response In Adcontrasting
confidence: 58%
“…49 Another report suggested no difference in response to donepezil or rivastigmine treatment according to BCHE genotype. 50 Further investigation of the response to ChEI therapy across a range of AD severities associated with APOE and BCHE genotypes is warranted. 29 The objective of this study was to determine whether APOE or BCHE genotype predicts cognitive response to ChEI therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the cholinergic system is a logical target for pharmacogenomic studies. There have been several studies on possible associations between genetic polymorphisms of cholinergicrelated genes and the therapeutic effect of AChEIs [10,11]. However, there are limitations as follows in those previous studies.…”
Section: Association Of the Choline Acetyltransferase Gene With Respomentioning
confidence: 99%
“…In the present study we have examined the polymorphic variations of the genes encoding 3 enzymes involved in the synthesis, transport, and metabolism of acetylcholine in the cholinergic system ( • ▶ Fig. 1) [11,12]. Choline acetyltransferase (ChAT) encoded by the gene CHAT synthesizes acetylcholine, using choline and acetyl-CoA as substrates [11].…”
Section: Association Of the Choline Acetyltransferase Gene With Respomentioning
confidence: 99%
See 1 more Smart Citation